2003
DOI: 10.1029/2003ja009940
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the He+ layer observed over Arecibo during solar maximum and solar minimum with CTIP model results

Abstract: [1] Light ion concentration observations from the Arecibo incoherent scatter radar have shown regions of He + layering in the topside ionosphere in the postmidnight hours. The He + layering phenomenon has been observed during both solar maximum and solar minimum conditions. During solar maximum the layer is well defined, giving maximum relative abundances of over 50%. The observational results also show regions of He + dominance in the topside ionosphere during solar maximum in the height range 750-1200 km. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…As a result, He + tends to concentrate in a layer at and above the O + ‐H + transition region throughout the night. Wilford et al [2003] have found that the CTIP model required modification to accurately produce He + concentrations that agreed with observational data taken at Arecibo. They found He + constituted up to 57% of the postmidnight ion composition under solar maximum conditions.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…As a result, He + tends to concentrate in a layer at and above the O + ‐H + transition region throughout the night. Wilford et al [2003] have found that the CTIP model required modification to accurately produce He + concentrations that agreed with observational data taken at Arecibo. They found He + constituted up to 57% of the postmidnight ion composition under solar maximum conditions.…”
Section: Introductionmentioning
confidence: 60%
“…While the data taken at Arecibo [ Erickson and Swartz , 1994; Wilford et al , 2003; Gonzalez et al , 2004] showed higher values of the He + fraction, it should be noted that those measurements were taken throughout a night over an altitude range while at a fixed latitude and longitude. The data presented here are fixed in altitude and local time, while covering all latitudes and longitudes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transition height, h t , between the O + dominated ionosphere and the H + dominated protonosphere, collapses following sunset as seen in Figure A1c. This collapse is associated with the formation of a He + layer near h t ( Figure A1d), which forms under ambipolar diffusion and attains a maximum peak density near 0400 LT [González and Sulzer, 1996;Wilford et al, 2003;González et al, 2004].…”
Section: A1 Ionospheric Density Temperature and Velocitymentioning
confidence: 99%